INFLUENCE OF EMPLOYEE ATTITUDES ON EMPLOYEE PERFORMANCE IN NZOIA SUGAR COMPANY IN BUNGOMA COUNTY, KENYA - Ochieng , Micheal Musa; Okumu, Otsyulah (IJRDO - Journal of Business Management, 2023)
The success or failure of this organization depends on their culture, which is always regarded as their asset or liability. Thus, the purpose of the study was to establish the influence of employee attitudes on employee performance in Nzoia sugar company in Bungoma County, Kenya; The study adopted a descriptive survey research design, with a target population of 335 people; which comprised of 326 employees and 9 heads of departments. The sample size of 181 persons was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and interview guides. The instruments were validated by the experts in the area of study. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) was analysed for the two scores and found to be 0.79; thus the instruments were reliable. Quantitative data was analysed using descriptive statistics and presented in tables, while qualitative data was presented using quotation. The study established that employee attitudes had a statistically significant association with employee performance. It was therefore recommended that for enhanced employee performance there should be a clear understanding of the employee attitudes. It is hoped that the findings of the study will also help management develop strategies appropriate to manage employee attitudes and performance across the sugar industries.